Strategi Pembelajaran Experential Learning terhadap Peningkatan Akademik Siswa di SD Muhammadiyah Abepura - Talabudin Umkabu; Nur'im Septi Lestari (LP. Ma'arif Janggan Magetan, 2023)
The purpose of this research is to determine the impact of experiential learning strategies on academic improvement among students at SD Muhammadiyah Abepura. The method used in this research is qualitative research with a field study approach. This type of research is typically conducted through observation, interviews, or measurements and sampling. The research was conducted at SD Muhammadiyah Abepura. The results of this research indicate that the experiential learning model is implemented by teachers at SD Muhammadiyah Abepura through experiencing, observing, reflecting, and providing structured experiences supported by the natural environment, 3R (Reduce, Reuse, Recycle) facilities, an observatory, and various types of plants and trees that grow within the school environment. These elements serve as learning resources for the students. Additionally, teachers provide worksheets that need to be filled out as a result of observations, and they evaluate students' activities through movement assessments. Furthermore, self-assessment is conducted, where students assess themselves and share their evaluation. Based on these evaluations, teachers can draw conclusions regarding students' learning achievements, using the evaluation results as a measure of students' success in their learning activities. In summary, the research findings highlight that the implementation of the experiential learning strategy at SD Muhammadiyah Abepura involves hands-on experiences, observation, reflection, and structured experiences supported by various environmental resources. Worksheets are used to document observations, and evaluation is carried out through assessing students' active participation. Self-assessment is also conducted, enabling students to evaluate themselves. The evaluation results are then used as indicators of students' learning success.